O mito da democracia racial e a mestiçagem no Brasil (1889-1930) - Domingues, Petrônio (Diálogos Latinoamericanos, 2005)
In this article, we show that, on the plan of ideas, the racial democracy myth was progressively built in the transcourse of the Colony Brazil and the Empire. In dawning of the Republic, it was common sense to consider the Brazilian society deprived of any kind of racial barrier. Thus, Gilberto Freyre's largest merit, when releasing Casa Grande & Senzala, in 1933, was not “to discover” a supposed opportunity equality among blacks and whites, but to have transformed it into the official racial ideology of the country. Besides that, we make an assessment of the crossbreeding in the Brazilian racial system, having São Paulo as stage of our concerns, in the historical cutting of the First Republic (1889-1930).